Prickly ash seeds can promote healthy production of sheep by regulating the rumen microbial community - Li, Dengpan; Li, Qiao; Ma, Xueyi; Wang, Huihui; Wang, Chunhui; Wang, Haoyu; Liu, Zhanjing; Li, Taotao; Ma, Youji (Frontiers in Microbiology, 2024)
This study aimed to investigate the effect of prickly ash seeds (PAS) on the microbial community found in rumen microbes of Hu sheep by adding different percentages of prickly ash seeds and to carry out research on the relation between rumen flora and production performance. Twenty-seven male lambs of Hu sheep were classified into three groups based on the content of prickly ash seeds (PAS) fed for 90 days, i.e., 0%, 3%, and 6%. At the end of the feeding trial, rumen fluid samples were collected from six sheep in each group for 16S amplicon sequencing. The results showed that the addition of prickly ash seeds significantly increased both Chao1 and ACE indices (P < 0.05), and the differences between groups were greater than those within groups. The relative content of Bacteriodota decreased, and the relative content of Fusobacteriota, Proteobacteria, Acidobacteriota, and Euryarchaeota increased. The relative content of Papillibacter and Saccharofermentans was increased at the genus level, and the relative content of Bacteroides and Ruminococcus was decreased. The test group given 3% of prickly ash seeds was superior to the test group given 6% of prickly ash seeds. In addition, the addition of 3% of prickly ash seeds improved the metabolism or immunity of sheep. Fusobacteriota and Acidobacteriota were positively correlated with total weight, dressing percentage, and average daily gain (ADG) and negatively correlated with average daily feed intake (ADFI), feed-to-gain ratio (F/G), and lightness (L*). Methanobrevibacter and Saccharofermentans were positively correlated with ADG and negatively correlated with ADFI and L*. In conclusion, under the present experimental conditions, the addition of prickly ash seeds increased the abundance and diversity of rumen microorganisms in Hu sheep and changed the relative abundance of some genera. However, the addition of 6% prickly ash seeds may negatively affect the digestive and immune functions in sheep rumen.